Institute of Dedication to the State in the Study of Organizational Communication Patterns - Nuryanto, Guyub; Sariyati, Sariyati; Kuncoroyakti, Yohanes Arie; Fajar, Abdul Malik (Review: Journal of Multidisciplinary in Social Sciences, 2024)
Communication is the most important aspect to build organizational integrity because it can determine the effectiveness and smooth direction of communication that occurs in the organization. The title of this research is "Institutions for State Service in the Study of Organizational Communication Patterns". This study determines the pattern of organizational communication within the Dedication to the Country institution. The research method used in this study is a qualitative method with a descriptive approach. The data used in this study comprised primary data and secondary data. Primary data is as information got from interviews with several informants. While secondary data is as data got from books and other sources. The theory used in this scientific writing research is the theory of Organizational Culture Theory. The data collection techniques used are interviews, observations, and online data searches. The results of this scientific writing research are known that the communication pattern used by dedication institutions to the country is formal communication and informal communication, both of which are used in horizontal and vertical communication. This research uses a qualitative approach with a descriptive approach and a constructivist paradigm. Interviews were conducted with 10 resource persons comprising 1 founder, 4 daily management bodies, and 4 steering committees. Organizational culture theory became an important basis for this study. The organizational culture in Dedication to the Country uses more family systems. The media used in this organization in disseminating information often uses social media such as Facebook, Instagram, TikTok. The problem that often arises is the existence of members and volunteers when communicating.